Soziale Arbeit und soziale Frage(n) - Blumenthal, Sara-Friederike; Lauermann, Karin; Sting, Stephan (Schriftenreihe der ÖFEB-Sektion Sozialpädagogik, 2018)
The current social changes are leading to a resurgence of the "social question". At the same time, migration and flight or calls for inclusion are provoking social reactions. This volume examines the associated new challenges and perspectives for professional action in social work.